Holding ability determines 54% of air rifle shooting scores - Ihalainen, S.; Kuitunen, S.; Mononen, K.; Linnamo, V. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Air rifle shooting studies have focused on holding ability and postural balance (Ball et al. 2003, Konttinen et al. 1999). Other technical aspects, such as aiming accuracy and cleanness of triggering, have not been studied in air rifle shooting. Therefore, the aim of this study was to identify the most important performance determining factors in elite-level air rifle shooting.